Traits of orthorexia nervosa and the determinants of these behaviors in elite athletes - Surala, O.; Malczewska-Lenczowska, J.; Sadowska, D.; Grabowska, I.; Bialecka-Debek, A. (Nutrients, 2020)
Background: The purpose of this study was to evaluate the traits of orthorexia nervosa (ON) and its relation to body composition and anthropometric indices among elite athletes. Methods: We studied 273 (125 female, 148 male) competitive athletes. ON was assessed with the self-administered ORTO-15 questionnaire. Total body composition was determined using dual-energy X-ray absorptiometry (DXA). Results: The ORTO-15 score was independent of sex, type of effort or age. The ORTO-15 score was related to: total body mass (TBM) (p = 0.037; R = 0.170), body mass index (BMI) (p = 0.022; R = 0.187), bone mineral content (BMC) (p = 0.035; R = 0.172), lean soft tissue (p = 0.026; R = 0.182) and visceral adipose tissue (VAT) (p = 0.007; R = 0.255) in the male; BMI (p = 0.045; R = 0.412) and BMC (p = 0.012; R = 0.506) in weight-dependent male athletes. There was no relationship between ORTO-15 score and body composition in the total study group and subgroup of female athletes. In female athletes, ON tendencies were related to the weekly training time (p = 0.039), but in sprint and high-intensity intermittent efforts subgroup exclusively. Conclusions: Factors related to ON tendencies concerned exclusively BMI and body composition in male, and the weekly training time in female athletes. The results from this study demonstrate that a significant percentage of athletes, irrespective of sex, age, type of sport or hours of training per week, may manifest traits of orthorexia nervosa.